Analysis of Factors associated with Revision of Ventriculoperitoneal shunt at National Institute of Neurological and Allied Science, Nepal - Yogi, Nikunja; Thulung, Suraj; Munakarmi, Mayush Bahadur; Nakarmi, Rachana; Gongal, Dinesh Nath (Nepal Journal of Medical Sciences, 2019)
Introduction: Ventriculoperitoneal (VP) shunt is the commonest procedure for hydrocephalus. The cases requiring shunt revision is a major obstacle in its management. Various factors have been implicated for failure or revision of shunt like patient’s age, sex, cause of hydrocephalus, duration of surgery. This study aims to analyze the rate of VP shunt revision and various factors associated with it. Methods: In this study, we analyzed 237 cases aged three months to 75 years, of VP shunt from January 2010-December 2014 with at least one year follow up at National Institute of Neurological and Allied Sciences. We evaluated the rate of VP shunt revision and various factors associated with it. The categorical variables were evaluated by chi-square test. Odds ratio was calculated for each factors at 95% CI. Results: There were 54 (22.78%) cases having at least one revision within one year of shunt insertion. The odds of revision of shunt was 6.58 times higher when inserted through frontal approach than occipital approach. The external ventricular drain placement prior to shunt surgery had statistically significant association with shunt revision (p=0.02). There was no difference in patients requiring/not requiring shunt revision when compared in terms of age group, gender, various etiologies and side of shunt insertions. Conclusions: The rate of shunt revision in our study was 22.78% which is comparable to other studies. Frontal approach in VP shunt insertion was associated with increased rate of shunt failure thus requiring revision. Likewise, external ventricular drain placement prior to shunt surgery was associated with increased incidence of revision surgery.